Endoscopic Ultrasound-Guided Tissue Acquisition in Solid Pancreatic Lesions: Fine Needle Aspiration or Fine Needle Biopsy—A Randomized Pilot Study from a Low-Resource Tertiary Care Center - Nayak, Hemanta Kumar; Gupta, Shubham; Chaudhary, Mansi; Ahari, Kamlesh; Kar, Saswati; Patra, Susama; Mishra, Pritinanda; R.U, Ajay Ghosh; Pattnaik, Bramhadatta; Patel, Ranjan Kumar; Panigrahi, Manas K.; Samal, Subash Chandra (Journal of Digestive Endoscopy, 2025)
Solid pancreatic mass lesions pose a substantial diagnostic challenge, especially in resource-limited settings. Endoscopic ultrasound (EUS)-guided fine-needle aspiration (EUS-FNA) and fine-needle biopsy (EUS-FNB) are both widely utilized, yet comparative data on their performance under constrained conditions remain limited.In this prospective, randomized, single-center pilot study, patients with suspected solid pancreatic lesions were randomized to undergo either EUS-FNA (n = 20) or EUS-FNB (n = 21). Diagnostic accuracy, sensitivity, specificity, sample cellularity, technical success, adverse events, and total cost (needle + pathological processing) were assessed.Forty-one patients were randomized. Diagnostic accuracy was slightly higher in the FNB group (95.2%) compared to the FNA group (90%). Sensitivity was similar for FNB (92.9%) and FNA (92.3%), but specificity was greater with FNB (100% vs. 85.7%). Technical success was 100% in both arms, with only minor adverse events reported. Most samples demonstrated moderate to high cellularity in both arms. The estimated cost per procedure was INR 22,200 for FNA and INR 27,400 for FNB.EUS-FNB demonstrated slightly improved diagnostic yield but was expensive compared to FNA. In resource-limited settings, EUS-FNA offers a cost-effective and reliable first-line diagnostic option. Larger multicenter studies are needed to guide context-appropriate needle selection strategies.
Keywords: endoscopic ultrasound; fine-needle aspiration (FNA); fine-needle biopsy (FNB); adenocarcinoma; pancreatic cancer